Characterizations of fuzzy fated filters of R0-algebras based on fuzzy points - Kavikumar, J.; Young, Bae Jun; Akram, Muhmmad (2017)
More general form of the notion of quasi-coincidence of a fuzzy point with a fuzzy subset is considered, and generalization of fuzzy fated of R0-algebras is discussed. The notion of an (∈,∈∨ qk)-fuzzy fated filter in a R0-algebra is introduced, and several properties are investigated. Characterizations of an (∈, ∈ ∨ qk)-fuzzy fated filter in an R0-algebra are discussed. Using a collection of fated filters, a (∈,∈∨ qk)-fuzzy fated filter is established.